2022
DOI: 10.1186/s12866-022-02653-4
|View full text |Cite
|
Sign up to set email alerts
|

Fruit bagging reduces the postharvest decay and alters the diversity of fruit surface fungal community in ‘Yali’ pear

Abstract: Background Fruit bagging is an effective technique for fruit protection in the orchard management. Bagging can create a micro-environment for fruit growth and affect fruit quality during storage, in which the diversity of microorganisms may play an important role. Therefore, various methods including biochemistry, analytical chemistry, and bioinformatics methods were used to reveal the influences of fruit bagging on postharvest fruit quality, physiological characters, decay and surface fungal c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 43 publications
1
3
0
Order By: Relevance
“…The high prevalence of Ascomycota in both cultivars may be attributed to Ascomycota's non-fastidious nature, which enables it to thrive in tough environments with low nutrition levels [54]. Although Ascomycota have been found to be plant-and insect-pathogenic fungi [55] and corroborated with findings from a variety of plants and fruits, including grapes, cherries and pear [56][57][58][59]. Thus, may justify why it predominates over other fungi phylum as observed in this study.…”
Section: Discussionsupporting
confidence: 80%
“…The high prevalence of Ascomycota in both cultivars may be attributed to Ascomycota's non-fastidious nature, which enables it to thrive in tough environments with low nutrition levels [54]. Although Ascomycota have been found to be plant-and insect-pathogenic fungi [55] and corroborated with findings from a variety of plants and fruits, including grapes, cherries and pear [56][57][58][59]. Thus, may justify why it predominates over other fungi phylum as observed in this study.…”
Section: Discussionsupporting
confidence: 80%
“…6C). Research has shown that Lactarius and Coprinellus can promote seed germination and seedling development, while Mortierella and Vishniacozyma have the potential for pollution remediation and pathogen resistance (Gao et al 2022a;Gao et al 2022b;Wang et al 2022b). The substantial enrichment of these fungi can enhance the growth of oilseed rape, with a more pronounced effect observed on the aboveground biomass.…”
Section: Discussionmentioning
confidence: 99%
“…High-quality fruits have been increasingly popular in recent years, and TA and SSC are two significant determinants of fruit quality [7]. SSC and TA changes could be attributed to the conversion of sugars and acids during fruit ripening [19]. The type and content of soluble sugars in fruits not only determine the flavor and quality of the fruit, but they are also important energy substances, intermediates, and important substrates of many metabolic pathways, and they play a role in the regulation of plant growth, ripening, and senescence as signaling molecules in many processes; for example, the delay of fruit senescence was related to the maintaining of higher energy status in apple fruit [20].…”
Section: Discussionmentioning
confidence: 99%